Seccess is the Enemy of Experimentation - Hidayati, Sri (Esensi: Jurnal Bisnis dan Manajemen, 2014)
In a competitive world, the raising demands to perform good governance are urgency. Learning is essential requirement to organisation to sustain existence and get success. However, success sometimes defined differently by different people. Success which is defined as stability more likely would impede the experimentation (a learning process). By using the perspective of organization culture, this paper tries to assess and contextualize the claim from Levitt and March (1988) that “Success is the Enemy of Experimentation” to organizational learning. This paper is provided by an empirical case study  of  a university based research organisation and is try to contribute to a more complete understanding of organizational learning.